MINIMALLY INVASIVE SURGERY FOR PSEUDOPAPILLARY NEOPLASM OF THE PANCREAS - NAMUR, Guilherme Naccache (Arq Bras Cir Dig, 2016)
BACKGROUND: Solid pseudopapillary pancreatic neoplasia is usually a large well-circumscribed pancreatic mass, with cystic and solid areas more frequently found in young women. It is a benign pancreatic neoplasia in most cases, therefore minimally invasive surgery could be an interesting approach. AIM: Evaluate the results of minimally invasive surgery for this neoplasia. METHODS: Patients with this tumor who underwent minimally invasive pancreatectomies between 2009 and 2015 in a single institution, were analyzed regarding demographic, clinical-pathological futures, post-operative morbidity and disease-free survival. RESULTS: All were women, and their median age was 39 (18-54) years. Two patients with tumor in the head of the pancreas underwent laparoscopic pancreaticoduodenectomy, and another one underwent laparoscopic enucleation. Two patients with tumor in the neck underwent central pancreatectomy. Distal pancreatectomies were performed in the other five, one with splenic preservation. None required blood transfusion or conversion to open surgery. Two (20%) developed clinical relevant pancreatic fistulas, requiring readmission. Median length of postoperative hospital stay was five days (2-8). All resection margins were negative. Patients were followed for a median of 38 months (14-71), and there was no recurrence. CONCLUSIONS: Minimally invasive surgery for solid pseudopapillary pancreatic neoplasia is feasible for tumors in different locations in the pancreas. It was associated with acceptable morbidity and respected the oncologic principles for treatment.